Assessing Accessibility in MOOCs: A Comparison of Moodle and Coursera for Users with Hearing Impairments, Visual Impairments, and the Elderly - Sato, Mariana H. K.; Silva, Felippe F. da; Amaral, Aline M. M. M.; Leal, Gislaine C. L.; Guerino, Guilherme C.; Balancieri, Renato (Anais do Workshop sobre Educação em Computação (WEI), 2025)
With technological advancements, Massive Open Online Courses (MOOCs) have become widely adopted, supporting course management and content delivery. However, many platforms still face accessibility challenges due to inconsistent adherence to guidelines. This study evaluates the accessibility of Moodle and Coursera using WCAG 2.0, the WAVE tool, and Nielsen’s Heuristics. A mixed-methods approach combines qualitative and quantitative analyses. Results show that while Moodle demonstrates better overall accessibility, Coursera is more suitable for elderly and visually impaired users. This research contributes to digital accessibility and offers practical recommendations to enhance inclusion in MOOCs.